2019
DOI: 10.1152/ajpheart.00487.2018
|View full text |Cite
|
Sign up to set email alerts
|

BMI1 promotes cardiac fibrosis in ischemia-induced heart failure via the PTEN-PI3K/Akt-mTOR signaling pathway

Abstract: Cardiac fibrosis has been known to play an important role in the etiology of heart failure after myocardial infarction (MI). B lymphoma Mo-MLV insertion region 1 homolog (BMI1), a transcriptional repressor, is important for fibrogenesis in the kidneys. However, the effect of BMI1 on ischemia-induced cardiac fibrosis remains unclear. BMI1 was strongly expressed in the infarct region 1 wk post-MI in mice and was detected by Western blot and histological analyses. Lentivirus-mediated overexpression of BMI1 signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…They regulate not only metabolic processes such as protein synthesis and glycolysis/gluconeogenesis [32,33] but also cell growth, cycle progression and cell division, proliferation, and apoptosis [34][35][36][37]. Currently, the PI3K pathway is receiving increasing attention, and far more significant functions are being revealed [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…They regulate not only metabolic processes such as protein synthesis and glycolysis/gluconeogenesis [32,33] but also cell growth, cycle progression and cell division, proliferation, and apoptosis [34][35][36][37]. Currently, the PI3K pathway is receiving increasing attention, and far more significant functions are being revealed [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These are the essential cellular pathways of mitochondrial protein synthesis, significantly relevant to the cardiac remodeling and heart failure [53,54]. Furthermore, pathways of programmed cell death (e.g, Apoptotic Execution Phase) and PTEN regulation (e.g., Regulation of PTEN Stability and Activity), which were previously reported as important factors of cardiac remodeling and homeostasis [53,5558], were detected solely by DCEC in two-directional and one-directional change clusters, respectively. Supplemental Tables S6–S8 list the unique pathways enriched by K-means, HC, PAM, LSTM-VAE, and DCEC in one-directional change, two-directional change and late change clusters, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our present study found that miR-132 targeted PTEN in CFs, which is supported by previous study [ 22 ]. The signal pathway of PI3K/Akt was involved in the fibrosis of the heart [ 37 , 38 ]. The expression of p-Akt was increased in the CFs treated by Ang II [ 8 ].…”
Section: Discussionmentioning
confidence: 99%